Enhancing Quality and Productivity in Software Engineering: An Ontology-Driven Prescriptive Agile Framework - T., Deepa; S., Thaddues; G., Dhamodharan (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The prescriptive agile framework is a novel approach that leverages an integrated process ontology, involving agile Scrum and OpenUp methodologies. The objective is to enhance both productivity and quality within software development projects where fresh developers are engaged. Key Process elements of OpenUP and agile Scrum are used to construct the ontology. The ontology is defined and instantiated with software projects having the complete user stories. Subsequently a three-sprint project experiment is conducted. The metrics of Earned Value (EV) and Code Maintainability are used to gauge productivity and quality. This research contributes to improving productivity and code quality in software engineering particularly when there are many amateurs.